Enhancing MSME Financial Performance Through Strategic Capabilities: The Mediating Role of Managerial Decision-Making - Yayu Rakkang; Andi Nur Achsanuddin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are vital to economic growth but often face challenges in financial sustainability and decision-making effectiveness. This study aims to examine how financial literacy, accounting technology utilization, and entrepreneurial orientation influence MSME financial performance, with managerial decision-making as a mediating variable. Using a quantitative research design, data were collected from 222 MSMEs in Makassar City through structured questionnaires and analyzed using Structural Equation Modeling with SmartPLS. The results reveal that accounting technology utilization and entrepreneurial orientation have significant direct effects on financial performance. Financial literacy, while not directly associated with financial outcomes, significantly influences performance through managerial decision-making. This mediating role highlights that the strategic application of financial knowledge is more impactful than financial literacy alone. Conversely, technology and entrepreneurial behavior tend to bypass structured decision-making processes, indicating a need for better integration of these capabilities into managerial frameworks. These findings contribute to existing knowledge by integrating cognitive, technological, and behavioral factors into a unified performance model. The study emphasizes that empowering decision-making capacities enhances the value of internal resources. Policymakers and business advisors are encouraged to adopt holistic development strategies that combine literacy, digital tools, and strategic judgment to strengthen MSME competitiveness.